Influence of plasmonic array geometry on non-radiative energy transfer from a quantum well to a quantum dot layer - Bradley, Louise (IEEE, 2017)
The influence of ordered plasmonic arrays on energy transfer from a quantum well to a quantum dot layer has been investigated. The ordered arrays are comprised of nanostructures of different geometries, including boxes, disks and rings. Despite no signature of non-radiative energy transfer in the absence of an array, an efficiency of ~51% is observed for a ring array, though strong emission quenching yields an overall increase of only ~ 14% of the QD emission. The QD emission is enhanced by ~25% for disk arrays, and was found to be relatively insensitive to the gap between disks. In contrast, the QD emission enhancement decreases from ~70% to 40% as the separation between boxes increases from 100 nm to 160 nm. The largest increase in QD emission of ~70% is due to a non-radiative energy transfer efficiency of ~25% coupled with a QD emission enhancement factor of ~1.4. The results demonstrate the flexibility offered by plasmonic arrays to optimise non-radiative energy transfer or to benefit from a combination of energy transfer and enhanced radiative emission, relevant to sensing and colour conversion applications.
19th International Conference on Transparent Optical Networks (ICTON)
Keywords: Plasmonics; Non-radiative energy transfer; Quantum dots; Förster resonance energy transfer (FRET); Down conversion; Quantum well